2014
DOI: 10.1186/1471-2474-15-360
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three plate system for lateral malleolar fixation

Abstract: BackgroundThis study was to compare clinical and radiographic outcomes with three different implants and evaluate the effectiveness of minimally invasive plate osteosynthesis (MIPO) technique for the distal fibular fractures.MethodsWe performed a retrospective cohort single-surgical team single-facility study between 2000 and 2011. 147 patients receiving surgical interventions for closed, displaced distal fibular fractures were included. Based on the different implants, patients were divided into three groups:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 25 publications
1
28
1
1
Order By: Relevance
“…Because the incision scar exactly coincided with the head of the screw, it was not difficult to remove the screw with the mini incision. The present AOFAS values are observed to be better than those from Chiang et al, 1 Pires et al, 6 and Huang et al 4 However, in the present study, all of the patients had isolated lateral malleolar fractures, and in these three publications, patients had other ankle trauma in addition to lateral malleolar fractures. In studies that present only lateral malleolar fracture open surgery results, the AOFAS scores are close to the present results.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…Because the incision scar exactly coincided with the head of the screw, it was not difficult to remove the screw with the mini incision. The present AOFAS values are observed to be better than those from Chiang et al, 1 Pires et al, 6 and Huang et al 4 However, in the present study, all of the patients had isolated lateral malleolar fractures, and in these three publications, patients had other ankle trauma in addition to lateral malleolar fractures. In studies that present only lateral malleolar fracture open surgery results, the AOFAS scores are close to the present results.…”
Section: Discussioncontrasting
confidence: 66%
“…It was observed that in the literature studies of fixation of the malleolus lateralis with a percutaneous plate, an external guide was not used. 1,[4][5][6][7][8] With the present technique, an equal-sized plate was used as an external guide. With this technique, the use of an equal-sized plate as an external guide ensured less exposure to fluoroscopy during determination of the incisions and screwing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, for OTA 44-B and 44-C lateral malleolar fractures, the biomechanical superiority of locked lateral plates cannot be demonstrated when compared with conventional lateral plates in a meta-analysis of biomechanical studies using osteoporotic cadaver models [29]. Up to date, there are several studies evaluating the clinical outcomes in lateral malleolar fractures treated with and without locking plates [3,4,13,22,23,26,[30][31][32] (Supplemental Table 3). However, the reported results vary under the different inclusion criteria for fracture type and implant type.…”
Section: Association Of Clinical Features With Faos and Vas Scoresmentioning
confidence: 99%